PENGARUH PERLAKUAN PANAS (HEAT TREATMENT) DENGAN VARIASI QUENCHING TERHADAP KELELAHAN DAN KEKERASAN BAJA ST 41 - Razak , Zainal Arman; fajar, fajar; Suryanta, Dhanu (POLITALA PRESS, 2025)
ST 41 steel is a low carbon steel, has a relatively low surface hardness, so it requires additional heat treatment to improve resistance to wear and cyclic loads. This study aims to examine the effect of variations in cooling media on the mechanical properties of ST 41 steel, especially hardness and fatigue resistance. The variations in cooling media used were water, SAE 20W-50 oil, and air at a temperature of 950°C with a holding time of 15 minutes. The heat treatment process includes preheating and hardening, followed by quenching using the three media. The results showed that the hardness of the steel increased significantly after heat treatment, with the highest value in water cooling (171 HV). In fatigue testing, untreated ST 41 steel showed 71,651 cycles, while heat treatment with oil, air, and water reduced the number of fatigue cycles to 30,571.67, 19,461, and 43,402.33 cycles